In Vitro Activity of Ticarcillin Against Anaerobic Bacteria Compared with That of Carbenicillin and Penicillin - Roy, Ira (1977)
A total of 334 clinical anaerobic isolates were tested in an anaerobic glove box by the agar dilution technique for susceptibility to clinically achievable levels of ticarcillin, carbenicillin, and penicillin. Thirty-two micrograms or less of penicillin per milliliter inhibited 91% of all strains, whereas 100 μg of carbenicillin and ticarcillin per ml inhibited 95 and 98%, respectively. A total of 82% (85 strains) of Bacteroides were inhibited by penicillin, and 93 and 96% were inhibited by carbenicillin and ticarcillin, respectively. Thirteen (24%) of 55 strains of Bacteroides fragilis tested were resistant to 32 μg of penicillin per ml, and 6 (11%) and 3 (5%) were resistant to 100 μg of carbenicillin and ticarcillin per ml, respectively. Within the therapeutic range, ticarcillin was the most effective of the three penicillins tested against B. fragilis subsp. fragilis.